The use of financial derivative, corporate governance, Shariah compliance and firm value: evidence from Malaysia, Indonesia, Bangladesh and Thailand - Yao, Junyi (2019)
This study aims to examine the relationship between the use of financial derivatives and firm value with consideration of corporate governance and Shariah-compliance factors by analyzing the non-financial firms in Malaysia, Indonesia, Bangladesh and Thailand during the period between 2010 to 2017. Firstly, a general analysis is done in overall countries and found out that the use of financial derivatives has negative and insignificant relationship with the firm value. However, after taken account into corporate governance factor, the impact turned out to be positive. This shows that the corporate governance factor has some influence towards the impact of financial derivatives on the firm value. Secondly, the analysis is separately done in each country, and the results show that there is a positive and significant relationship between the use of financial derivatives and firm value under a strong corporate governance structure. In order to further analyze the different characteristic between the Shariah-compliant companies and non-Shariah-compliant companies. Under the assumption that the Shariah-compliant companies have a stronger corporate governance structure compared with non-Shariah-compliant companies. A total of 89 Shariah-compliance companies are chosen as the matching counterparties for the 89 conventional companies in Malaysia. And a total of 66 conventional companies are chosen as the matching counterparties for the 66 Shariah-complaint companies in Indonesia. The result shows that the Shariah-compliant companies with stronger corporate governance can obtain a derivative premium, however, the non-Shariah-compliant companies with weaker corporate governance obtain a derivative discount.